AL-QUR’AN DAN HADIS SEBAGAI SUMBER HUKUM ISLAM - Septi Aji Fitra Jaya (JURNAL INDO-ISLAMIKA, 2019)
National and state life cannot be separated from legal regulations. As a religious community, it is appropriate to obey the legal orders stipulated in a teaching, just as Islam also has rules and laws that must be obeyed by its adherents. The source of law in Islam is the al-Qur'an and Sunnah, the words of Allah and the Sunnah of the Prophet which are the main foundation in Islamic teachings. Understanding of the two sources of law is important because they cannot be separated from one another, there is a relationship between the two in explaining the applicable laws in Islam. So it is proper to understand the two sources of law to be the main thing, if there is an error in understanding between the two, it will damage the existence of the source of the law. By understanding the two sources of law, namely al-Qur'an and Hadith, you will get legal instructions that are in accordance with the guidance of the Shari'a and sunnah of the prophet Muhammad. This paper describes the existence between the two sources of Islamic law in its application in a pluralistic society, using thematic methods.